Former Yugoslav Republic of Macedonia : Issues in Urban and Municipal Development - World Bank (Washington, DC, 2014)
The present study examines the challenges facing municipal governments in FYR Macedonia. The introductory chapter provides some further context for these developments, in terms of the challenges they pose for urban areas and their governments. Chapter Two examines issues for financial management of municipalities under the decentralized regime, and the attendant need for improving local government capacity. The third chapter highlights questions in the area of communal services, where municipal governments retain overall provision and supervisory responsibilities of the local public enterprises. The fourth chapter focuses on urban planning and land management, an area critical to the efficient functioning of cities and for which municipalities have acquired new obligations. The approach of the report is to assemble existing data from many available studies, both by the World Bank and by other sources, and information obtained from interviews in the country to articulate ideas and recommendations for consideration by the Government elected in July 2006, by municipal governments, and by other stakeholders.